2023
DOI: 10.1111/jdv.19586
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis suppurativa associated telomere‐methylome dysregulations in blood

Uppala Radhakrishna,
Uppala Ratnamala,
Devendrasinh D. Jhala
et al.

Abstract: BackgroundHidradenitis suppurativa (HS) is a chronic debilitating disease with a significant burden of both organic and psychological comorbidities. It has been shown that certain telomere‐related genes (TRGs) affect a wide range of diseases, including HS and its associated comorbidities, but their exact role in HS pathogenesis is still unknown.ObjectivesTo determine whether TRG methylomes can be used as biomarkers in HS.MethodsUsing the Illumina HumanMethylation450 BeadChip array, we examined methylation vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Gene PLCB1 has been reported to be involved in the pathogenesis of neurological diseases and also as cancer-promoting in various tumors, including colorectal cancer [ 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Interestingly, PLCB1 was also identified in the blood methylome analysis of hidradenitis suppurativa (HS) patients [ 92 ]. It is known that HS and CD are both chronic inflammatory diseases, and a high fraction of CD patients are also diagnosed with HS [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene PLCB1 has been reported to be involved in the pathogenesis of neurological diseases and also as cancer-promoting in various tumors, including colorectal cancer [ 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Interestingly, PLCB1 was also identified in the blood methylome analysis of hidradenitis suppurativa (HS) patients [ 92 ]. It is known that HS and CD are both chronic inflammatory diseases, and a high fraction of CD patients are also diagnosed with HS [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the epigenetic modulation of tissue-specific genes could contribute to the structural changes and to the recurrent nature of HS lesions [36]. Radhakrishna et al [45] also investigated telomere-related genes (TRGs) methylomes in whole bloodderived genomic DNA of HS patients to assess their role in HS pathogenesis, reporting 585 differentially methylated sites in 585 TRGs (474 hypomethylated and 111 hypermethylated). TRGs act on multiple pathways such as DNA repair, telomere maintenance, mismatch repair, and cell cycle control, and their disruption led to the telomeres shortening, which is associated with HS progression, aging, cellular senescence, and an increased risk of cancer and associated comorbidities, such as metabolic syndrome, cardiovascular disease, and inflammatory disorders.…”
Section: The Role Of Dna Methylationmentioning
confidence: 99%
“…The role of miRNAs in the pathogenetic scenario of HS was supported by the research of Hessam et al [53], demonstrating a significant decrease in the expression of principal regulators of miRNAs maturation in the affected skin of HS patients [54] (Figure 2C). The same authors reported that the biogenesis and mechanism of action of miRNAs in HS patients were characterized by pronounced dysregulation leading to an abnormal inflammatory response, aberrant keratinocyte proliferation, and impaired wound healing [45,54]. In detail, Hessam et al [54] demonstrated that Drosha and Dicer, RNA processing enzymes required for the maturation of miRNAs, and the RNA-induced silencing complex (RISC) were downregulated in lesional HS patients' skin samples.…”
Section: The Role Of Micrornas and Long Non-coding Rnamentioning
confidence: 99%
“…Epigenetic studies highlighted a dysmethylation background for HS patients, which disrupts cell aging and functionality, inflammatory response, and drug metabolism, consequently altering the cutaneous immune system–microbiome homeostasis [ 6 , 7 , 8 , 9 ]. Thus, a more detailed understanding of cutaneous dysbiosis occurrence is of paramount importance to prevent disease progression and innovate a curative intervention instead of merely treatment.…”
Section: Introductionmentioning
confidence: 99%